Snowed in with the children's doctor - Heaton, Louisa (Harlequin medical romance, 2023)
Frosty beginnings... with a heartwarming ending? During a blizzard, Nell finds herself snowed in with her new colleague, grumpy pediatrician Seth. Following an icy start--and an inconvenient spark --Nell tries to keep her distance...until they're forced to appear as Santa and his elf on the children's ward Nell doesn't celebrate the season, not after all she's lost. And single dad Seth struggles at Christmastime too. Is this the year they let their boxed-up feelings be unwrapped?